PERCEPTUAL MECHANISMS FOR REPLACING OLD WORDS AND ADAPTING NEW WORDS: ESTABLISHING A CROSS-TALK BETWEEN WORD REPLACEMENT AND CODE-SWITCHING IN ODIA (Proceeding of the International Conference on Arts and Humanities, 2019)
This paper presents an investigation on how a decrease in perception determines the replacement of underuse old words, and the increase of perception manifests the adaptation of overuse new words. A relationship between lexical replacement and code-switching is established by examining the perceptual mechanisms of lexical adaptation in Odia. To test lexical adaptation in terms of perceptual rate, a psycholinguistic experiment on old Sanskrit tatsam and their semantic-equivalent English-borrowed words was conducted by using semantic-priming paradigm. Target words that were associated either positively and negatively with preceding Odia and English priming-words were presented in Odia orthography. Odia-English bilingual speakers were asked to comprehend the positive and negative association between target and priming words, and to respond by pressing left arrow-key for positive and right arrow-key for negative meaning. Measuring perceptual facilitation for adaptation and code-switching in terms of response time (ms), results show that disyllabic English-borrowed words are processed faster than their equivalent disyllabic Sanskrit-tatsam words. English negative priming words facilitate the processing of disyllabic Sanskrit-tatsam words, suggesting faster code-switching effect from English to Odia. Odia-English bilingual speakers have a tendency to adapt English disyllabic words in the place disyllabic Sanskrit-tatsam words, preserving the minimal disyllabic word structure of Odia.
Keywords: Lexical replacement; adaptation; borrowed words; semantic paradigm